MODEL OF INFRASTRUCTURE INFORMATION SYSTEM ON CIPTA KARYA DIVISION - Bennie Bennie (Jurnal Teknologi Berkelanjutan, 2013)
Manual data processing is difficult on data searching process if it is needed for the importance of planning, controlling interests, reporting purpose, monitoring and evaluation. The general weakness of collecting manual data processing is that it is difficult to search for input data and it is unable to provide maximum data services as well as high efficiency on data processing. The aim of this study is to improve data processing with a computerized system which can provide information services rapidly, efficiently and accurately. In providing maximum public services and the work efficiency in data processing and expediting the decision-making process a model of infrastructure information system is required from the Cipta Karya division. The system model is approached using a computer based information system (CBIS) as an option for a support system when applying the system approach. The system design utilised a data analysis technique SDLC (system development life cycle). The output of this model is a centralised database system which provides an up-to date information distribution, as well as a source of official information relating to the process of decision-making support. The system runs on a web-based network, so it is easily accessible using a browser. This system will give information about project history handling that can make it easier to make decisions on when and where the project will be programmed. Such a web-based application is one of the solutions that can be developed to accommodate the needs of the organization in an integrated manner.